Development and preliminary verification of a 1D–3D coupled flow and heat transfer model of OTSG - Lu, Xianghui; Wang, Xin; Zheng, Xiong; Chen, Xiting; Meng, Shuqi; Ruan, Tianming; Chen, Jun; Mao, Yulong; Hu, Yisong; Shang, Chaohao (Frontiers in Energy Research, 2024)
Introduction: A simulation model was developed by coupling a one-dimensional (1D) system code and 3D CFD software, to analyze the three-dimensional (3D) flow and heat transfer characteristics of the once-through steam generator (OTSG). Methods: The shell side of the OTSG was simulated by FLUENT, and the tube side was simulated by the system code LOCUST. Through spatial mapping, the 1D and 3D simulations were coupled along the outer wall of the OTSG's helically coiled tubes. Results and Discussion: This coupling method enabled the acquisition of high-resolution flow and heat transfer characteristics of the OTSG, and the error of heat flux calculation result by the coupled model is within 15%. Through coupling simulation analysis of the prototype OTSG, it was found that the inlet and outlet temperature difference reached as high as 150°C. The unevenness of the radial temperature distribution increased along the flow direction, and the wake swing effect caused by the sweeping flow of the tube bundle at the exit position was evident. The results of this study provide reference and a coupled simulation method for the engineering design and thermal-hydraulic characteristics analysis of OTSG.